ANALISIS KEMAMPUAN GURU AL-QURAN HADIS DALAM MENYUSUN RENCANAAN PELAKSANAAN PEMBELAJARAN (RPP) DI MIS AZ-ZUHRI TANJUNG MORAWA - Sitti Isni Azzaah; Siti Halimah (Universitas Islam Negeri Sumatera Utara Medan, 2022)
The purpose of this study was to determine the suitability of third-grade Al-Quran hadith teachers' lesson plans for MIS Az-zuhri Tanjung Morawa with the principles of development based on the 2013 Curriculum. The type of research used was Mix Methode research. By analyzing the data that has been collected, the results The results obtained from this study are that most of the five components presented in lesson plans include identity: in accordance with the writing procedure, competency components, analysis results: not appropriate, components of learning materials made by the teacher: in accordance with the material to be taught, learning steps: appropriate, assessment components: not appropriate. And the guidelines and reasons for Al-Quran Hadith teachers in compiling lesson plans at MIS Az-zuhri Tanjung Morawa are that there are still many teachers who make lesson plans by looking at guidelines from the internet, the reason being the lack of knowledge they have in compiling lesson plans. The conclusion is that not all of the Al-Quran Hadith teachers at the school are capable of making lesson plans and correctly according to the guidelines in the 2013 curriculum.